The Role of Dividend Policy in Shaping Market Value of Shares: Evidence from Colombo Stock Exchange. - Mithila, G.; Kengatharan, L. (South Asian Journal of Finance, 2025)
Purpose: This study investigates the role of dividend policy in determining the impact of dividend policy on the stock prices of the non-financial companies listed on the Colombo Stock Exchange in Sri Lanka during the period from 2017 to 2021, using panel data analysis. The research aims to explore the varies aspects of dividend policy that affect market prices in the Sri Lankan context. Design/Methodology/Approach: A sample of 90 non-financial firms, resulting in 450 observations, was selected for this study. To analyze the relationship between the independent variables namely dividend per share, dividend payout ratio and dividend yield and the dependent variable of market price per share, the study used pooled OLS, fixed and random effect models. After chow, Hausman, and LM tests, fixed effect model is selected as the best model for the study. Findings: These results indicate a positive and significant relationship between dividend per share, dividend payout ratio and share price supporting signaling theory, and dividend relevance theory. Conversely, the study finds a significant negative relationship between dividend yield and stock prices, suggesting that higher dividend yields may limit a firm’s growth prospects by reducing reinvestment opportunities. Originality: This study contributes to the literature by applying panel data techniques to assess the influence of dividend policy on stock prices in an emerging market like Sri Lanka. It provides empirical evidence to support the relevance of dividend policy in shaping market perceptions and stock valuation. Theoretical and Policy Implications: The findings offer insights for academicians, corporate managers, investors, and policymakers. By understanding the importance of dividend policy and its impact on the market value of shares, stakeholders can make more informed decisions related to dividend distribution, market strategies, and corporate growth planning. Research limitations/ Future research directions: Future research could extend this study by exploring the effects of dividend policy on stock prices during pre and post financial crisis periods or by examining the moderating role of other financial variables such as leverage and earnings growth.
Keywords: Dividend per share; Dividend payout ratio; Dividend policy; Dividend yield; Market share price; Colombo Stock Exchange